2015
DOI: 10.1061/(asce)wr.1943-5452.0000540
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Climatic-Change Impacts on Multiobjective Reservoir Operation with Multiobjective Genetic Programming

Abstract: Multiobjective genetic programming is used to calculate optimal reservoir-operating rules under baseline and climatic-change conditions. The rules are calculated based on river inflows to the Aidoghmoush Reservoir (located in East Azerbaijan, Iran), storage volume, and downstream irrigation demands. The objective functions are the maximization of the reliability of meeting irrigation demand and the minimization of the vulnerability to irrigation deficits in a baseline period (1987-2000) and a future period (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Ashofteh, Bozorg Haddad, and Loaiciga () found that the ranges of vulnerability and reliability indices were larger under climate change conditions, in response to larger flow variability. They concluded that modified reservoir's rule curves under climate change may improve performance scores as compared with control period rules.…”
Section: Discussionmentioning
confidence: 99%
“…Ashofteh, Bozorg Haddad, and Loaiciga () found that the ranges of vulnerability and reliability indices were larger under climate change conditions, in response to larger flow variability. They concluded that modified reservoir's rule curves under climate change may improve performance scores as compared with control period rules.…”
Section: Discussionmentioning
confidence: 99%
“…The decision variables in Equation are the parameters that define the hedging rule for reservoir release introduced in Equation ; LSR = the long‐term shortage ratio; RSPH t = reservoir release (regulated release plus spill flow) calculated based on hedging rule during period t ; T = length of the operation interval; and D = average water demand during the operation interval.The hedging release rule depends on the reservoir's water availability according to Equation : RSPHt=f()AWt1emt=1,2,.,T in which f (AW t ) = hedging rule calculated with the TGP and LGP approaches; and AW t = available water during period t , which is calculated with Equation assuming linear approximation of reservoir evaporation (Fallah‐Mehdipour et al ., ; Ashofteh et al ., , b): AWt=St+Qtet()aSt+b10001emt=1,2,.,T in which S t = reservoir storage at the beginning of period t ; Q t = reservoir inflow during period t ; e t = depth of reservoir evaporation during period t ; and a and b = constants in the surface storage function of the reservoir.…”
Section: Methodsmentioning
confidence: 99%
“…In other research by Ashofteh et al . () multi‐objective genetic programming (MO‐GP) was implemented to calculate optimal reservoir‐operating rules under baseline and climatic change conditions. The objective functions were the maximization of the reliability of meeting irrigation demand and the minimization of the vulnerability to irrigation deficits under baseline condition and future conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have used a single GCM (Ashofteh et al, 2015;Fortier and Mailhot, 2015) or an ensemble mean from multiple climate models (Benestad, 2003;Smith et al, 2009;Tebaldi and Knutti, 2007). Using each approach, only one "likely" outcome was produced, but no information regarding a range of possible outcomes.…”
Section: Gcm Performance and Convergencementioning
confidence: 99%
“…The question here is how to choose an appropriate subset of GCMs. Studies choose a subset of GCMs based on results from earlier studies on the performance of the GCMs in simulating the local climate, future climate, or both (Ashofteh et al, 2015;Elhakeem et al, 2015;Singh et al, 2015). The number of GCMs selected in these studies ranges from one to nine.…”
Section: Gcm Performance and Convergencementioning
confidence: 99%